The association between increased body mass index and response to conventional synthetic disease-modifying anti-rheumatic drug treatment in rheumatoid arthritis: results from the METEOR database. (30th April 2021) - Dey, Mrinalini; Zhao, Sizheng S; Moots, Robert J; Bergstra, Sytske Anne; Landewe, Robert B; Goodson, Nicola J
Abstract: Background: Few data exist on the association between increased BMI and response to conventional synthetic DMARDs (csDMARDs) in RA. We aimed to explore the association between increased (overweight or obese) BMI on csDMARD prescribing, MTX dose and disease activity over 12 months. Methods: Participants in an international RA database were stratified into early (<1 year post-diagnosis) and established RA. EULAR response, 28-joint DAS (DAS28) remission and treatments were recorded at baseline, 6 months and 12 months. Increased BMI was explored in early and established RA as predictors of good EULAR response, DAS28 remission, number of csDMARDs and MTX dose, using logistic and linear regression. Results: Data from 1313 patients, 44.3% with early RA, were examined. In early RA, increased BMI was not significantly associated with remission. In established RA, obese patients on monotherapy were significantly less likely to achieve good EULAR response or DAS28 remission at 6 months and more likely to be treated with combination csDMARDs compared with normal BMI. In patients taking MTX, overweight and obese patients with early and established RA were exposed to higher MTX doses (mono- and combination therapy), with a mean dose of 20 mg/week, compared with 15 mg/week in those of normal BMI. Conclusion: We observed that compared with patients with normal BMI, overweight and obese individuals experienced more intensive csDMARD exposures. Similar response rates were observed in early RA but increased BMI was associated with reduced response in established RA. Optimization of targeted RA treatment remains important, particularly in those with increased BMI where response in established disease may be attenuated.